Ore-Forming Fluid Evolution in the Giant Gejiu Sn–Cu Polymetallic Ore Field, SW China: Evidence From Fluid Inclusions - Chen, Yongqing; Wang, Zhenyi; Li, Jiande (Frontiers in Earth Science, 2021)
The giant Gejiu Sn–Cu polymetallic ore deposit is one of the largest Sn producers in the world, and is related in time and space to highly evolved S type granitic intrusion. The mineralization processes can be divided into four stages: (I) skarnization; (II) greisenization; (III) cassiterite–sulfid; and (IV) cassiterite–tourmaline–quartz. Five types of fluid inclusions were recognized using optical petrography, microthermometry, and Raman spectroscopy. The results of microthermometry revealed the evolution of the ore-forming fluid, from a high temperature with low–to–high salinity to a low temperature with low–to–intermediate salinity. Stage I, skarn Sn–Cu ores were formed by bimetasomatism between the granitic intrusion and the surrounding rock under near–critical conditions with the help of ore-forming fluid. Stage II, the fluid was separated into the coexisting liquid and vapor phases in equilibrium condition, and a large amount of cassiterite–scheelite–beryl–lithium muscovite minerals were formed during greisenization. Stage III, mixing, boiling and immiscibility of different types of fluid solutions took place with a decline in temperature and pressure as well as a change in the Eh–pH, which caused huge amounts of cassiterites and sulfides to precipitate. Stage IV, stockwork ores characterized by cassiterite–tourmaline–quartz minerals were formed associated with the low temperature and low salinity hydrothermal liqiud activity. The laser Raman spectra identified CH4 in all ore-forming stages, indicating that the ore deposits might have been formed in a relatively reduced environment. CO2 appeared in all stages in addition to Stage I, and might have been formed due to both immiscibility of fluid solutions with dropping pressure as well as temperature and mixing of different types of fluid solutions. In conclusion, the bimetasomatism, mixing, and immiscibility of fluid solutions should have been responsible for the formation of giant Sn–Cu polymetallic deposits.